Field investigation and assessment on the wear of asphalt pavement milling machine picks - Sivilevičius, Henrikas; Martišius, Mindaugas (Transport, 2021)
Deteriorated asphalt pavement material is recycled applying proved technologies based on scientific principles and practical experience. The asphalt pavement layer during rehabilitation process is loosened by a mobile transport machine fracturing into the required material grading and called Reclaimed Asphalt Pavement (RAP). RAP is extracted while cutting asphalt chip in required depth at optimal speed by mean of changeable picks installed in a toolholder of milling machine rotating drum. During interaction with the asphalt pavement to be demolished, the wear of picks appears, and the dimensions of their elements decrease. Methodology and results of a field experimental research allowed statistically to determine and evaluate the wear dynamics of picks from 2 manufacturers are provided in this paper. The results provide that length of pick, diameter of carbide tip and diameter of steel body of picks from these manufacturers were decreasing proportionally to milled asphalt pavement surface. Applying the Fisher’s criterion it was found that the variances of the reduction of these geometrical parameters are the same and they satisfy the normal distribution according to the Kolmogorov’s criterion. All values of Student’s criterion calculated statistics were higher than the critical values, which indicated that the wear intensiveness of the picks of the 2 manufacturers differed significantly. These data can be used to select suitable picks for the milling machine according to their wear intensity. First published online 9 February 2022